An Analysis of Self Concept Writing Performance Found in the Students' Journal - Suprihatin, Yeni (Tapis: Jurnal Penelitian Ilmiah, 2018)
It has been widely accepted that writing is a productive skill in English language instruction. The students need to involve themselves mentally and physically. Indeed, cognitive, affective, and psychomotor domain have been believed to be crucial factors in writing instructions. This research, on the contrary dealt with the affective domain variable. Such variables as mental block, self confidence, and self concept were reflected with the students’ writing performance of English Department of STAIN Jurai Siwo Metro. The students’ perception toward writing subject caused the writer’s block. I believed that journal can be an alternative medium to solve the students’ mental block problem. Thus, this research mainly analyzed self concept of writing performance found in the students’ journal.